Numerical solutions of mixed convection boundary layer flow near the lower stagnation point of a horizontal circular cylinder in a nanofluid - Leony Tham; Roslinda Nazar; Ioan Pop (2013)
In this paper, the problem of steady mixed convection boundary layer flow in a nanofluid near the lower stagnation point of a horizontal circular cylinder in a stream flowing vertically upwards has been studied for both cases of a heated and cooled cylinder. The resulting system of nonlinear partial differential equations is solved numerically using an implicit finite-difference scheme known as the Keller-box method. Three different types of nanoparticles considered are Cu, Al2O3 and TiO2 by using water-based fluid. Numerical solutions are obtained for the skin friction coefficient and heat transfer coefficient as well as the velocity and temperature profiles with various values of the parameters, namely, the nanoparticle volume fraction φ and the mixed convection parameter λ at Prandtl number Pr = 6.2. © 2013 Pushpa Publishing House.